A Comparative Analysis of Hazardous Medical Waste Management Compliance Before (2019) and During (2020) the COVID-19 Pandemic in Indonesia - Andika Putri, Della Amanda; Zakianis; Aysary, Al; Softwan (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. As a producer of hazardous waste, hospitals have the responsibility to manage the waste they produce. Hospital non-compliance in managing hazardous waste can have a negative impact on the environment and public health, especially during the COVID-19 pandemic, when the amount of hazardous waste produced by healthcare facilities is increasing. To protect the environment and public health from the negative impact of hazardous medical waste, this study was conducted to determine the level of compliance of hazardous waste management in hospitals in Indonesia before and during the COVID-19 pandemic, from 2019 to 2020. Study design. Cross-sectional. Methods. This study was conducted at 343 hospitals in Indonesia using secondary data obtained from Sikelim (Medical Waste Management Information System), which is owned and operated by the Ministry of Health. The data have been analyzed using chi-square tests and logistic regressions of the determinant model. Results. There was an increase in the level of compliance of hazardous waste management in hospitals from 82% to 86% during the pandemic. Furthermore, the availability of environmental documents and environmental health units were determinant factors of hazardous waste management compliance by hospitals before the pandemic in 2019. The only factor in 2020 was the availability of environmental health units. Conclusions. Despite the good level of compliance, additional efforts are needed to increase the activities of the treatment of hazardous medical waste by hospitals, as before the pandemic (i.e., in a normal situation) only 8% of hospitals was able to independently manage hazardous medical waste using authorized incinerators, a percentage that was reduced to 6% during the pandemic.